2022
DOI: 10.3390/nu14153212
|View full text |Cite
|
Sign up to set email alerts
|

Bile Salt Hydrolase-Competent Probiotics in the Management of IBD: Unlocking the “Bile Acid Code”

Abstract: Bile acid (BA) species and the gut microbiota (GM) contribute to intestinal mucosa homeostasis. BAs shape the GM and, conversely, intestinal bacteria with bile salt hydrolase (BSH) activity modulate the BA pool composition. The mutual interaction between BAs and intestinal microorganisms also influences mucosal barrier integrity, which is important for inflammatory bowel disease (IBD) pathogenesis, prevention and therapy. High levels of secondary BAs are detrimental for the intestinal barrier and increase the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 147 publications
0
19
0
Order By: Relevance
“…Dietary supplementation with probiotics was demonstrated to modify the hosts’ BA pool and their metabolism. In fact, BSH-dependent BA debinding reduced the recycling of BAs and promoted their de novo synthesis, thereby reducing serum cholesterol levels . Jones et al found that BSH-competent bacteria in probiotic formulations changed the composition of BA and reduced serum cholesterol levels .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary supplementation with probiotics was demonstrated to modify the hosts’ BA pool and their metabolism. In fact, BSH-dependent BA debinding reduced the recycling of BAs and promoted their de novo synthesis, thereby reducing serum cholesterol levels . Jones et al found that BSH-competent bacteria in probiotic formulations changed the composition of BA and reduced serum cholesterol levels .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, probiotics containing active BSH strains are being used clinically in patients with IBD, enteritis, and diarrhea and may also be associated with patients with leaky gut secondary to liver disease (e.g., intrahepatic cholestasis) or colorectal cancer . So, tools that target BSH activity in microorganisms and intestinal flora are also particularly important .…”
Section: Discussionmentioning
confidence: 99%
“…BAs aid in the absorption of dietary fats and fat-soluble vitamins in the small intestine [ 92 , 93 ] and act as signaling molecules by binding to the farnesoid X receptor (FXR) and G protein­coupled bile acid receptor 1 [ 94 ]. This triggers molecular events impacting their own hepatic synthesis(via the action of the FXR-FGF19 duo) and glucose and lipid homeostasis [ 94 ].…”
Section: The Gut Microbiota and The Hostmentioning
confidence: 99%
“…BAs aid in the absorption of dietary fats and fat-soluble vitamins in the small intestine [ 92 , 93 ] and act as signaling molecules by binding to the farnesoid X receptor (FXR) and G protein­coupled bile acid receptor 1 [ 94 ]. This triggers molecular events impacting their own hepatic synthesis(via the action of the FXR-FGF19 duo) and glucose and lipid homeostasis [ 94 ]. As BAs and GM communicate with each other, disrupting this delicate balance can lead to intestinal barrier impairment, inflammation, and even contribute to cancer onset and development.…”
Section: The Gut Microbiota and The Hostmentioning
confidence: 99%
“…BAs have been demonstrated to modulate systemic lipid metabolism, glucose metabolism, and cholesterol as well as immune homeostasis through the interaction of these amphiphilic molecules with membrane and nuclear receptors, including farnesoid X receptors (FXRs) and Takeda G-protein-coupled receptor 5 (TGR5) [ 103 ]. The main bacterial species in the gut, such as Lactobacillus and Bifidobacterium taxa, express the enzyme bile salt hydrolase (BSH), which deconjugates BAs from glycine and taurine [ 104 ]. According to research, intestinal inflammation [ 105 ], metabolic disorders such as diabetes [ 106 ], and cardiovascular disease [ 107 ] are pathologically determined by gut microorganisms and abundant BSH genes.…”
Section: Mechanism Of the Interactions Between The Gut Microbiota And...mentioning
confidence: 99%